Efficacy and safety of autologous haematopoietic stem cell transplantation in systemic sclerosis: a systematic review of the literature. (1st March 2018) - Eyraud, A.; Scouppe, L.; Barnetche, T.; Forcade, E.; Lazaro, E.; Duffau, P.; Richez, C.; Seneschal, J.; Truchetet, M.‐E.; ,
Summary: Systemic sclerosis (SSc) is a rare condition in which the body's own immune cells attack the skin making it thick and tight. The lungs and kidneys may also be damaged and up to half of severely affected patients die within 5 years. Standard treatment with immune‐suppressive drugs, methotrexate or cyclophosphamide, is not always successful and can cause complications. An alternative is autologous haematopoietic stem cell transplantation (HSCT) in which cells able to multiply (stem cells) are extracted from the patient's blood or bone marrow, stored while the bone marrow is destroyed by chemotherapy, then infused back into the patient, to regenerate the bone marrow and populate the body with cells that have not been primed to cause auto‐immune disease. Using the patient's own cells means that anti‐rejection drugs are not required, but HSCT remains a risky procedure. To find out just how safe and effective autologous HSCT is in adults with SSc, this team from France searched the medical literature and identified 38 informative articles, including randomised and non‐randomised controlled trials and case series, covering 344 patients. Most studies showed a significant reduction in skin thickening, maintained for up to 8 years after HSCT. There was a slight improvement in lung function, measured as forced vital capacity, at 1 or 2 years. Death rate attributable to disease progression was 11%, to HSCT was 8.3% and to cyclophosphamide 1%. They conclude that the safety and efficacy of autologous HSCT in SSc are acceptable given the poor prognosis of this disease.